Exploring Non-Attitudinal Factors: The Role of Symbolic Meanings and Consumer Mindset in Driving Generation Z's Green Clothing Purchase Intention - Hanni Audi Chesyta Zihni; T. Ezni Balqiah (Sekolah Tinggi Manajemen IPMI, 2026)
This study examined the determinants of green clothing purchase intention among Indonesian Generation Z by integrating the Theory of Planned Behavior with symbolic meanings and consumer mindset. Data were collected from 384 respondents through an online survey and analyzed using Partial Least Squares Structural Equation Modeling. The results indicated that all dimensions of symbolic meanings, including environmentalism symbol, status symbol, innovation symbol, and fashion symbol, positively and significantly influenced attitude toward green clothing purchasing behavior. Environmentalism symbol showed the strongest effect on attitude. Attitude emerged as the most influential predictor of purchase intention, followed by subjective norm, while perceived behavioral control did not exhibit a significant effect. Mediation analysis confirmed that attitude partially mediated the relationships between symbolic meanings and purchase intention. In addition, moderation analysis demonstrated that consumer mindset significantly strengthened the influence of symbolic meanings on attitude, with stronger effects observed among consumers with a fixed mindset. Overall, the findings suggested that green clothing purchase intention among Generation Z was driven by a combination of symbolic interpretations, attitudinal evaluation, and cognitive orientation, highlighting the importance of symbolic and psychological factors in sustainable fashion consumption.